Response of Conservation Measures on the Growth of Planted Species and Improvement in Soil Properties in a Degraded Area - Banerjee, S. K.; Singh, A. K.; Jain, A.; Shukla, P. K. (Indian Forester, 2003)
Land degradation is a global phenomenon. Endless desires of man have put enormous pressure on this valuable natural resource. India is reported to have 175 million ha of land under various stages of degradation. Deforestation and improper land management are the main reasons. The great diversity in topographic conditions is responsible for an annual loss of about 6000 million tonnes of top fertile soil. Any improvement programme concerning soil health can not be achieved unless it incorporates soil and water conservation. Studies were conducted to assess improvement in soil properties due to adoption of soil-water conservation method (staggered trenching) on hilly slope in Jabalpur District of Madhya Pradesh , India. At site I Tectona grandis was planted at 2 m × 2 m spacing and in between rows staggered trenches of 3 m × 0.5 m × 0.5 m were dug. Observations recorded after 4.5 years of planting showed considerable improvement in soil properties , more so on the lower slope in respect of organic carbon , available nutrients (N , P and K) etc. Soil loss has also been reduced to a considerable extent. At site II Albizia procera and Albizia lebbek were planted and soil-water conservation measures were adopted in a similar way as at site I. This site also showed remarkable degree of improvement in soil properties at 4.5 years of age. Originally both sites were having highly eroded surface and the soil depth was as less as 15 to 20 cm underlain by hard rock and morrum. The soils were quite deficient in nutrients and were having low water building capacity. The growth of planted species was significantly higher than control.